Physicochemical evaluation of humus and compost as a strategy to strengthen sustainable agriculture - Manzano, Dennis; Parra, Vicente; Zurita, Susana; Pico, Máyuri (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Soil degradation due to unsustainable anthropogenic management has generated the deterioration of its quality and health, for this reason alternatives such as the use of organic fertilizers are sought for the rehabilitation of its ecological functions. Therefore, the present study evaluated the physical-chemical properties of humus and compost produced at the Tunshi experimental station, Chimborazo, Ecuador, in order to validate their suitability for sustainable agriculture. Formulations based on local inputs were used, including guinea pig manure, plant residues, green manure, and rice husks. The analyses included parameters such as pH, electrical conductivity (EC), organic matter (OM) and macronutrients, following the Ecuadorian standard NTE INEN 211:1998 and the INIAP technical manual. The results revealed that the compost and humus formulations comply with quality standards, highlighting the F2 compost formulation and the H2 formulation for humus with their high total nitrogen and OM content. The compost (F3) and humus (H3) formulations showed higher levels of phosphorus and potassium, although with lower nitrogen content, where F2 (35 % guinea pig manure, 25 % green manure) and H2 (50 % guinea pig manure, 50 % plant residues) showed higher nitrogen and OM content, while in F3 (25 % guinea pig manure, 30 % green manure) and H3 (40 % guinea pig manure, 60 % plant residues), there were no significant differences in the parameters of the humus formulations. These fertilizers represent a viable and sustainable agroecological alternative for the rehabilitation of degraded soils.